Performance analysis of web applications created in the Spring and Laravel frameworks - Jakub Suchanowski; Małgorzata Plechawska-Wójcik (Journal of Computer Sciences Institute)
The article compares the performance of two test applications created using the Spring Boot and Laravel application frameworks. The aim of the study is to find an answer to the research question: which framework offers better time performance. Twelve test scenarios were created for the analysis, and they were used to conduct performance tests using the Apache JMeter tool. Additionally, application metrics and community support for both frameworks were compared. The research confirmed that the application built on the Spring Boot framework has better performance.